Sejarah Konstruksi Sosial Pendidikan Islam - Ahmad Ali Riyadi (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2019)
This paper examines the social construction of Islamic education in terms of the historical periodization of the development of Islamic educational institutions. This study is important to analyze Islamic educational institutions in the history of the development of education and Muslim intellectuals objectively and comprehensively. In the span of history, the development of Islamic educational institutions has been constructed between the dialectic of Islamic missionary mission which has a connection with the culture of the community where it is located, so that there are variations in the forms of dynamic Islamic educational institutions